Gliadin Proteins in Muffins with Quinoa Flour - Vesna S. Gojković Cvjetković; Dragana M. Škuletić; Željka R. Marjanović-Balaban; Dragan P. Vujadinović; Danijela Z. Rajić; Vladimir M. Tomović (Техника и технология пищевых производств)
Partial replacement of wheat flour in foodstuffs is of great importance in the food industry. Muffins are a type of semi-sweet cake that is traditionally made from wheat flour. They are especially favored by children and senior citizens. Muffins have a long shelf life, which also contributes to their popularity. However, gluten, the main protein in wheat flour, is commonly associated with celiac disease. Gluten consists of two fractions: gliadins and glutenins. In this experiment, the original muffins contained 100% wheat flour. Then, we replaced a portion of wheat flour with 25, 50, and 75% quinoa flour. The samples were stored for 0, 2, and 4 weeks. After that, gliadin proteins were extracted with 70% (v/v) ethanol. We separated gliadin using a high-performance liquid chromatograph (Agilent Technologies 1260 Infinity, USA) and measured the total amount of gliadin protein and the amount of gliadin proteins per fraction. The absorbance tests were conducted at 210 nm. The gliadin protein content was significantly reduced to the wheat vs. quinoa ratio of 50:50 because quinoa is gluten-free, even though it is rich in protein. During the storage time of 0, 2, and 4 weeks, the protein content fell down in the samples with the wheat vs. quinoa ratios of 100:0, 75:25, and 50:50. However, the muffins with 25% wheat flour and 75% quinoa demonstrated an increase in gliadin content. The results obtained could be a good starting point for the development of high-fiber, gluten-free, and more nutritionally valuable muffins.